Small-scale variations in spider and springtail assemblages between termite mounds and the surrounding grassland matrix - Badenhorst, Hannelene; Haddad, Charles Richard; Janion-Scheepers, Charlene (Pensoft Publishers, 2024)
The snouted harvester termite (𝘛𝘳𝘪𝘯𝘦𝘳𝘷𝘪𝘵𝘦𝘳𝘮𝘦𝘴 𝘵𝘳𝘪𝘯𝘦𝘳𝘷𝘰𝘪𝘥𝘦𝘴 (Sjöstedt, 1911)) is a widespread grass-eating termite species that constructs thermoregulated dome-shaped mounds. However, little is known about the influence of these mounds on the arthropod assemblage structure in the surrounding grassland matrix, and whether the mounds represent ecological islands. Spiders and springtails are two ecologically important arthropod groups often associated with termites or their mounds. We investigated their assemblage composition inside and around active and abandoned T. trinervoides mounds in a central South African grassland. In total, 838 spiders (59 spp., 22 families) and 217 857 springtails (24 spp., 9 families) were collected from 96 pitfall traps, placed at four microhabitats in and around each of 12 active and 12 abandoned mounds during March 2019. The most abundant and species-rich spider families include the 𝘎𝘯𝘢𝘱𝘩𝘰𝘴𝘪𝘥𝘢𝘦 (n = 270, 10 spp.), 𝘡𝘰𝘥𝘢𝘳𝘪𝘪𝘥𝘢𝘦 (n = 86, 7 spp.), 𝘓𝘺𝘤𝘰𝘴𝘪𝘥𝘢𝘦 (n = 86, 6 spp.) and 𝘚𝘢𝘭𝘵𝘪𝘤𝘪𝘥𝘢𝘦 (n = 77, 5 spp.), whereas the springtail fauna was dominated by 𝘉𝘳𝘢𝘤𝘩𝘺𝘴𝘵𝘰𝘮𝘦𝘭𝘭𝘪𝘥𝘢𝘦 (n = 56 521, 1 species), 𝘉𝘰𝘶𝘳𝘭𝘦𝘵𝘪𝘦𝘭𝘭𝘪𝘥𝘢𝘦 (n = 49 573, 7 species), 𝘚𝘮𝘪𝘯𝘵𝘩𝘶𝘳𝘪𝘥𝘪𝘥𝘢𝘦 (n = 44 491, 3 species), 𝘐𝘴𝘰𝘵𝘰𝘮𝘪𝘥𝘢𝘦 (n = 32 288, 1 species) and 𝘌𝘯𝘵𝘰𝘮𝘰𝘣𝘳𝘺𝘪𝘥𝘢𝘦 (n = 26 216, 7 species). Indicator analysis showed that the spiders 𝘡𝘦𝘭𝘰𝘵𝘦𝘴 𝘴𝘤𝘭𝘢𝘵𝘦𝘳𝘪 Tucker, 1923, 𝘏𝘦𝘭𝘪𝘰𝘤𝘢𝘱𝘦𝘯𝘴𝘪𝘴 𝘵𝘦𝘳𝘮𝘪𝘵𝘰𝘱𝘩𝘢𝘨𝘶𝘴 (Wesołowska & Haddad, 2002) and 𝘚𝘤𝘺𝘵𝘰𝘥𝘦𝘴 𝘦𝘭𝘪𝘻𝘢𝘣𝘦𝘵𝘩𝘢𝘦 Purcell, 1904 are associated with abandoned mounds, but no springtails showed an association based on the IndVal analysis of the eight microhabitats (lumped data), even though the undescribed 𝘊𝘺𝘱𝘩𝘰𝘥𝘦𝘳𝘶𝘴 sp. were mostly collected inside active mounds. The mounds thus had a negligible influence on the spatial distribution of springtails in the surrounding grassland. The different spider and springtail assemblages sampled indicate that both active and abandoned mounds function as ecological islands in grasslands, but that mound size does not affect their abundance or species richness in the different microhabitats sampled.